Tactical Decision-Making Analysis via the Keep or Drop Method at Citra Gading Medika Clinic - Kurniasari, Sinta; Puspita W, Yustika; Pandin, Maria Yovita R (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Company managers are faced with several business operations problems that require tactical decision-making. One method of tactical decision-making is the keep or drop method, in maintaining or discontinuing a product or business division. Like the Citra Gading Medika clinic, facing a decline in turnover in skin and genital poly services, this requires tactical decision-making. This research aims to explain costs, analysis of tactical decision-making, and consideration of quality factors in the management of a business. The method used is a qualitative approach through case studies. Data collection uses secondary data and primary data. Secondary data was obtained from clinic financial reports. Meanwhile, the primary data used is through interviews and observations. The results of this research conclude that there are four alternatives that clinics can use in implementing the keep or drop method. From the results of calculating the benefits of each alternative, the best decision is to stop services at skin and genital polyclinics but shift its service capacity to increase polygenic services by 20%. This was chosen because it provides the greatest benefits for the clinic.